Production of acid-degummed castor oil from castor beans by supercritical fluid extraction by propane a plant design - Dela Rosa, Adriane Carlos P.; Samaniego, Arman Louie P.; Tibon, Jojo S.; Mariano, Victor B.; Baynosa, Marjorie L. (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
The proposed pilot plant is involved in the extraction of Castor oil from Castor Beans or Ricinus Communis. There are four common species of castor plant in the Philippines but the variety that contains the highest amount of oil by mass is the Brazilian type which has an oil content of approximately 49.3 percent by mass. Castor oil and its derivatives have application in industries such as Food, Textile Chemicals, Paper, Lubricants and Biofuels. The final product of the plant would be degummed castor oil and Pressed Castor Oil. Castor Bean has been widely accepted as an agricultural solution for all subtropical and tropical locations that addresses the need for commercial crops with low impute costs and at the same time provides traditional farming with a viable income from current non-productive lands: (Dove Biotech Ltd. 2003) Castor Bean does not compete with food crops, as castor bean can be grown on marginal lands, which are not competitive with food production lands.Castor Bean is not competing with food grade oils. Its toxicity is sensed by animals and therefore not foraged on. It is high yielding, yielding as much as 350-650 kg of oil per hectare when no maintenance is applied to the crop i.e. fertilizers etc, to a high end yield where annual rainfalls happen at the right times (1000 liter per hectare). It has a very high oil content of approximately 50 percent. The oil seed is collected by hand, by picking the ripe pods from the plant. It requires only moderate rainfall (approx. 600 mm only) and can withstand long periods of drought, but will thrive under higher rainfall. It is an uncomplicated crop that requires little attention during its growing periods. Due to its low demand on soil fertility, it is ideal to replant marginal lands to prevent desertification and erosion. Given the similar geographical, climatic and lack of rural employment opportunities, growing a crop for renewable energy provides the answer for long term prosperity. It is generally accepted that no matter how much oil seed is produced, there will not be an oversupply for many decades to come The plant will process 6000 tons of castor beans and would produce 2,224.15 tons of castor oil products annually which could translate to Php 144,523,260. The total capital investment for the plant is Php 83,072,324 and the gross earnings will be Php 41,188,467. The rate of return on investment is 32.23 percent.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Castor oil; Factories -- Design and construction